KLASIFIKASI EMOSI TOKOH UTAMA MIZUKI ASHIYA DALAM DRAMA HANAKIMI - Gusti Ayu Made Yuni Mahadewi; Made Henra Dwikarmawan Sudipa (Jurnal Daruma : Linguistik, Sastra dan Budaya Jepang, 2023)
This article aims to determine the emotional classification of the main character Ashiya Mizuki in the Japanese drama titled Hanakimi. The theory used is David Krech's theory of emotional classification. The data source used is the primary data source, using methods namely listen and record. Based on the results of the analysis of the data obtained, there are 4 types of classification of emotions, namely: basic emotions, emotions related to sensor stimulation, emotions related to oneself, and emotions related to others.